Synovial Cyst Mimicking an Intraspinal Sacral Mass. (4th March 2014) - Hoover, Jason; Pirris, Stephen
Abstract : A 68-year-old female had a three-week history of severe low back pain radiating down the posterior left buttocks and left leg exacerbated by standing and walking. Lumbar spine MRI revealed cystic mass with similar intensity to cerebrospinal fluid located on dorsolateral left side of the sacral spinal canal inferior to the S1 pedicle. There was compression of left exiting S1 and traversing S2 nerve roots. Neurosurgery consult was requested to evaluate the cystic mass in the sacral spinal canal. After clinical evaluation, an unusually located synovial cyst was thought possible. Cyst contents were heterogeneous, suggestive of small hemorrhage and acute clinical history seemed reasonable. Left S1 and partial left S2 hemilaminectomy was performed and an epidural, partially hemorrhagic cyst was removed. There was no obvious connection to the ipsilateral L5-S1 facet joint. Pathology revealed synovial cyst, and the patient's leg pain was improved postoperatively. This synovial cyst was unusual as it had no connection with the facet joint intraoperatively and its location in the sacral canal was uncommon.